The role of IMDb online community engagement on the motivation and intention to watch movies - Ribeiro, Catarina Alexandra Barreira (2020)
Nowadays, internet and social media are a necessity and indispensable tools that many businesses depend on. Conscious consumers before any consideration, rely on the online channel to search for reviews and ratings before the purchase. Within the entertainment industry the same is depicted. Movie enthusiasts before watching a movie rely on online brand communities' websites, such as IMDb, that have information about the quality and what to expect before watching a movie. IMDb - which is the exampled platform used on this study - is full of detailed reviews and ratings given by other members, defining engagement as the main pillar for this platform to succeed. Although, there is a lack of empirical studies that connect both entertainment consumption and online brand communities. This dissertation comes to fill this gap by analysing the concepts of Online Brand Communities Engagement within IMDb and the Motivation and Intention to Watch Movies. Also conceptualizing drivers of these concepts such as Brand Influence, Validation, Hedonic Motivation, and other moderators. The results prove that all drivers play a role in IMDb Online Brand Community Engagement, Motivation to Watch Movies and Intention to Watch Movies, indicating the existence of a positive relationship between the variables studied. Moreover, both drivers Hedonic Motivation and Eudaimonic Motivation have a positive impact on the Intention to watch movies. In conclusion, IMDb Online Brand Community engagement positively influences the Motivation to Watch Movies, which positively influence the further intention to watch them and the reliability on keeping following IMDb recommendations.